Peran Masyarakat Dalam Pengembangan Wisata Bahari Di Pantai Duta Wisata Bandar Lampung - Enny Mulyantari; Setyo Prasiyono Nugroho; Natalia Artemisia Sancia (STIE Pariwisata API Yogyakarta, 2025)
Duta Wisata Beach in Bandar Lampung is a marine tourism destination that has great potential to be developed. However, the development of marine tourism in the area is still not optimal, one of the contributing factors is the minimal role of the community in the development of marine tourism. This study aims to identify and analyze the role of the community in the development of marine tourism at Duta Wisata Beach, Bandar Lampung. This study uses a qualitative approach method, determining informants with a purposive sampling technique totaling three people. The results of the study indicate that the role of the community is very important in the development of marine tourism at Duta Wisata Beach. The roles that can be carried out by the community are first, as an initiator, namely as a trigger and driver in realizing ideas and thoughts. Second, as an implementer, namely the community carries out operational activities. Third, as a companion, namely the contribution and responsibility of the community in maintaining the beauty and cleanliness of the surrounding environment. Fourth, as a reviewer, namely the community supervises the process and impact of tourism development. Fifth, as a beneficiary, namely increasing community welfare in the economy.